Analiza problemów tłumaczeniowych konstytucji Grecji na język polski - Ciesielczyk, Natalia (Investigationes Linguisticae, 2009)
The subject of this article is the analysis of problems in the translation of the Greek Constitution into Polish which was published by the Publishing House of the Polish Parliament (Wydawnictwo Sejmowe) in 2005. This text was not translated directly from Greek but from its French and English versions. I attempt to prove that this is the main reason why it contains so many incorrect translations, presenting a selection of classified mistakes found in the Polish text and comparing them with analogical parts of the Greek original text as well as of its French and English versions. I give also some suggestions of correct Polish equivalents for a number of Greek legal terms used in the text of the Greek Constitution.